Pest Strips—You Have to Read the Fine Print - Frederick Fishel (EDIS)
Pest strips are commonly sold at many retail outlets and are available to anyone for purchase. They are constructed of resin plastic with an insecticide that is gradually control-released over time as a vapor. This 2-page fact sheets gives important tips on how to use pest strips correctly without creating a hazard. Written by Fred Fishel and published by the UF Agronomy Department, April 2016.